1993
DOI: 10.1038/bjc.1993.391
|View full text |Cite
|
Sign up to set email alerts
|

Depletion of circulating cyst(e)ine by oral and intravenous mesna

Abstract: Summary The sulfhydryl status of normal and tumour cells is critically important in determining their susceptibility to various cytostatic agents. As a sulfhydryl compound, mesna (sodium 2-mercaptoethanesulfonate) which is used in large doses to prevent haemorrhagic cystitis associated with certain chemotherapeutic regimens might derange cellular thiol homeostasis. In order to investigate the effects of mesna on the concentrations of thiols in plasma, cysteine, glutathione and their disulfides were measured by… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
17
0

Year Published

1994
1994
2008
2008

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(18 citation statements)
references
References 12 publications
1
17
0
Order By: Relevance
“…Total and oxidized glutathione concentrations in mitochondria were determined by a spectrophotometer using the methods of Tietze [25] and Griffith [26], respectively. Sulfhydrils (cysteine, GSH, GSHE) in plasma and liver were measured by HPLC following derivatization of SH groups with monobromobimane [27,28]. ALT in plasma was assessed using an automated procedure.…”
Section: Methodsmentioning
confidence: 99%
“…Total and oxidized glutathione concentrations in mitochondria were determined by a spectrophotometer using the methods of Tietze [25] and Griffith [26], respectively. Sulfhydrils (cysteine, GSH, GSHE) in plasma and liver were measured by HPLC following derivatization of SH groups with monobromobimane [27,28]. ALT in plasma was assessed using an automated procedure.…”
Section: Methodsmentioning
confidence: 99%
“…As with dimesna, these disulphides can be reduced to mesna and cysteine, which are then excreted into the urine (Jones et al 1985;StoferVogel et al 1993b;Wright et al 1985). Cysteine is able to react with ifosfamide metabolites in the same manner as mesna and, thus, cysteine is also 451 involved in regional detoxification (Shaw 1987;Stofer-Vogel et al 1993b).…”
Section: Prevention Of Urotoxicity By Administration Of Thiolsmentioning
confidence: 96%
“…However, its influence on renal tubular toxicity, which is only observed after administration of multiple highdoses of ifosfamide, remains unclear (Goren et al 1989;Stofer-Vogel et al 1993b). No data from clinical studies comparing administration of ifosfamide with and without mesna are available.…”
Section: Prevention Of Urotoxicity By Administration Of Thiolsmentioning
confidence: 96%
“…Several studies have demonstrated that mesna depletes plasma thiols such as cysteine and tHcy in patients who undergo chemotherapy. Stofer-Vogel et al (46) were the first to report that oral and intravenous mesna deplete the thiol amino acid cysteine by enhancing its urinary excretion. Similarly, Lauterburg et al (33) and Pendyala et al (34) showed depletion of tHcy by intravenous infusion of mesna to patients who were undergoing concurrent chemotherapy with ifosfamide.…”
Section: Discussionmentioning
confidence: 99%